Outcomes of Primary 27-Gauge Vitrectomy for 73 Consecutive Cases With Uveitis-Associated Vitreoretinal Disorders - Kim, Kyung Woo; Kusuhara, Sentaro; Imai, Hisanori; Sotani, Noriyuki; Nishisho, Ryuto; Matsumiya, Wataru; Nakamura, Makoto (Frontiers in Medicine, 2021)
Background: Since the advent of 27-gauge microincision vitrectomy system a decade ago, evidence regarding the feasibility, safety, and effectiveness of 27-gauge pars plana vitrectomy (PPV) has increased. Aim: To assess the effectiveness and safety profile of 27-gauge PPV for various vitreoretinal conditions associated with uveitis. Methods: We retrospectively investigated 73 consecutive cases that underwent primary 27-gauge PPV for uveitis-related ocular disorders between October 2014 and April 2021. The primary outcome measures were mean change in logMAR best-corrected decimal visual acuity (BCVA) pre-operatively to 3 months post-operatively, the proportion of BCVA improvement category defined as the degree of logMAR BCVA difference (“improved” [≤−0.3], “unchanged” [−0.3 to 0.3], and “worsened” [≥0.3]) pre-operatively to 3 months post-operatively, the mean change in intraocular inflammation scores pre-operatively to 3 months post-operatively; and intraoperative and post-operative complications. Results: The mean logMAR BCVA significantly improved from 0.69 pre-operatively to 0.42 at 3 months post-operatively (P = 0.017). The percentages of eyes with “improved,” “unchanged,” and “worsened” BCVA at 3 months post-operatively were 37, 50, and 13%, respectively. The mean anterior chamber cell score was 0.6 pre-operatively and 0.2 at 3 months post-operatively (P = 0.001), the mean anterior chamber flare score was 0.4 pre-operatively and 0.1 at 3 months post-operatively (P = 0.004), and the mean vitreous haze score was 1.9 pre-operatively and 0.1 at 3 months post-operatively (P < 0.001). Surgery-related complications occurred in 35 (48%) eyes, 68% of which were related to intraocular pressure and transient. Conclusions: Given its risk–benefit profile, 27-gauge PPV is a promising option for the treatment of vitreoretinal disorders in uveitis.